Comparison of capacitive and radio frequency resonator sensors for monitoring parallelized droplet microfluidic production. Issue 17 (6th July 2016) - Conchouso, David; McKerricher, Garret; Arevalo, Arpys; Castro, David; Shamim, Atif; Foulds, Ian G.
Abstract : Measuring the dielectric properties of emulsions using capacitive or RF resonator sensors can provide a quality control method for industrial-scale droplet production. Abstract : Scaled-up production of microfluidic droplets, through the parallelization of hundreds of droplet generators, has received a lot of attention to bring novel multiphase microfluidics research to industrial applications. However, apart from droplet generation, other significant challenges relevant to this goal have never been discussed. Examples include monitoring systems, high-throughput processing of droplets and quality control procedures among others. In this paper, we present and compare capacitive and radio frequency (RF) resonator sensors as two candidates that can measure the dielectric properties of emulsions in microfluidic channels. By placing several of these sensors in a parallelization device, the stability of the droplet generation at different locations can be compared, and potential malfunctions can be detected. This strategy enables for the first time the monitoring of scaled-up microfluidic droplet production. Both sensors were prototyped and characterized using emulsions with droplets of 100–150 μm in diameter, which were generated in parallelization devices at water-in-oil volume fractions ( φ ) between 11.1% and 33.3%.Using these sensors, we were able to measure accurately increments as small as 2.4% in the water volume fraction of the emulsions. Although both methods rely on the dielectric properties of the emulsions, the main advantage of the RF resonator sensors is the fact that they can be designed to resonate at multiple frequencies of the broadband transmission line. Consequently with careful design, two or more sensors can be parallelized and read out by a single signal. Finally, a comparison between these sensors based on their sensitivity, readout cost and simplicity, and design flexibility is also discussed.